Mucosal-Associated Invariant T-Cells: New Players in Anti-Bacterial Immunity - Ussher, James E.; Klenerman, Paul; Willberg, Chris B. (Frontiers in Immunology, 2014)
Mucosal-associated invariant T (MAIT) cells are an innate-like T cell population involved in antibacterial immunity. In humans, MAIT cells are abundant, comprising 10% of the CD8+ T cell compartment in blood. They are enriched at mucosal sites and are particularly prevalent within the liver. MAIT cells are defined by the expression of a semi-invariant T cell receptor (Vα7.2-Jα33/12/20) and are restricted by the non-polymorphic, highly evolutionarily conserved MHC class Ib molecule, MR1. MR1 has recently been shown to present an unstable pyrimidine intermediate derived from a biosynthetic precursor of riboflavin; riboflavin biosynthesis occurs in many bacteria but not in humans. Consistent with this, MAIT cells are responsive to riboflavin-metabolizing bacteria, including Salmonella. In mouse models, MAIT cells have been shown to play a non-redundant role in antibacterial immunity, including against E. coli, Klebsiella pneumoniae, and Mycobacterium bovis BCG. In humans, MAIT cells are decreased in frequency in the blood of patients with tuberculosis or pneumonia, and their frequency has been inversely correlated with the risk of subsequent systemic bacterial infection in patients in intensive care. Intriguingly, MAIT cells are also depleted from the blood early in HIV infection and fail to recover with antiretroviral therapy, which may contribute to the susceptibility of patients infected with HIV to certain bacterial infections, including with non-typhoidal Salmonella. In this review we will discuss what is currently known about MAIT cells, the role that Salmonella has played in elucidating MAIT cell restriction and function, and the role MAIT cells might play in the control of Salmonella infection.